2020
DOI: 10.1136/bjophthalmol-2019-315432
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography-based consensus definition for lamellar macular hole

Abstract: BackgroundA consensus on an optical coherence tomography definition of lamellar macular hole (LMH) and similar conditions is needed.MethodsThe panel reviewed relevant peer-reviewed literature to reach an accord on LMH definition and to differentiate LMH from other similar conditions.ResultsThe panel reached a consensus on the definition of three clinical entities: LMH, epiretinal membrane (ERM) foveoschisis and macular pseudohole (MPH). LMH definition is based on three mandatory criteria and three optional ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(172 citation statements)
references
References 34 publications
4
157
0
3
Order By: Relevance
“…This variable did not show any statistically significant impact on the postoperative visual outcome. After evaluation according to the definition of ERM made by Haubschman et al, however, we found true ERM with traction on macula in only 2% of patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variable did not show any statistically significant impact on the postoperative visual outcome. After evaluation according to the definition of ERM made by Haubschman et al, however, we found true ERM with traction on macula in only 2% of patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERM was recorded as well as any presence of irregular and hyper-reflective layer over the internal limiting membrane, regardless of whether there were signs of retinal wrinkling or not. These data were evaluated based on the consensus of OCT definition of ERM by Hubschman et al [ 33 ]. At the same postoperative visit, functional outcomes were recorded by determining BCVA.…”
Section: Methodsmentioning
confidence: 99%
“…Their other proposed subtype tractional LMH does not involve any actual tissue loss, the pathomorphologic changes caused by traction and therefore the panel proposed to name it as 'ERM foveoschisis' . Hubschman et al also proposed that thick ERM/dense ERM/atypical epiretinal tissue/LHEP be named 'epiretinal proliferation' [10]. Although the term LHEP is widely used we agree that it is not precise as the material has been found in conditions other than LMHs in full thickness macular holes (FTMH)s and at extrafoveal sites following trauma iatrogenic and accidental [7].…”
Section: Introductionmentioning
confidence: 90%
“…ERM traction can cause foveoschisis and the appearance of an irregular foveal contour that can be confused with LMH [10]. The pathogenesis of is similar to that of macular pseudoholes where the morphologic changes are cause by tractional forces exerted by the overlying ERM [4].…”
Section: Natural History and Historical Reviewmentioning
confidence: 99%
See 1 more Smart Citation